2011
DOI: 10.3945/jn.111.145805
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Retinol-Binding Protein Predicts Plasma Retinol Concentration in Both Infected and Uninfected Cameroonian Women and Children

Abstract: Variation in the relationship between plasma retinol-binding protein (RBP) and retinol (ROH) has implications for vitamin A (VA) status assessment using RBP. Our objectives were to identify factors affecting the RBP:ROH relationship and to derive and evaluate population-specific RBP cutoffs for VA deficiency (VAD) in Cameroon. Plasma RBP, C-reactive protein (CRP), α1-acid-glycoprotein (AGP), and ROH concentrations were compared in a subsample of women 15-49 y (n = 121) and children 12-59 mo (n = 123) included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 29 publications
0
73
1
Order By: Relevance
“…‡Fe deficiency is defined as serum ferritin <15 ng/ml (49) . §Adjusted for elevated C-reactive protein (>10 mg/l) or elevated α 1 -acid glycoprotein (>1 g/l) by mathematical correction (18,19) . ||Fe-deficiency anaemia is defined as Hb <11·5 g/dl plus serum ferritin <15 ng/ml in children aged 6-11 years and as Hb <12 g/dl plus serum ferritin <15 ng/ml in children aged 12-14 years (49) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…‡Fe deficiency is defined as serum ferritin <15 ng/ml (49) . §Adjusted for elevated C-reactive protein (>10 mg/l) or elevated α 1 -acid glycoprotein (>1 g/l) by mathematical correction (18,19) . ||Fe-deficiency anaemia is defined as Hb <11·5 g/dl plus serum ferritin <15 ng/ml in children aged 6-11 years and as Hb <12 g/dl plus serum ferritin <15 ng/ml in children aged 12-14 years (49) .…”
Section: Resultsmentioning
confidence: 99%
“…Adjusting for infection Serum ferritin was adjusted for infection by estimating biomarkers of infection: CRP and AGP. The adjustment of serum ferritin for elevated CRP (>10·0 mg/l) (15)(16)(17) and AGP (>1·0 g/l) was done by calculating the correction factors following the methods described by Thurnham et al (18) and Engle-Stone et al (19) . Similarly correction factors for serum retinol and Zn were calculated and used to adjust the retinol and Zn levels in serum.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…However, in 2009 a national survey was done in preparation for a large-scale food fortifi cation program (mandatory fortifi cation of oil) and indicators of VA status and infl ammation were assessed before the fortifi cation was begun. Adjusted results showed that 35 % of children under 5 years had VAD, which thus remains a severe public health problem [15]. These results suggest that the efforts through the national supplementation program have not been suffi cient to improve VA status in the population's children.…”
Section: Cameroonmentioning
confidence: 82%
“…However, a primary short-coming of RBP is the lack of universally acceptable cutoff for defining VAD, hence making comparisons and interpretations of results across different populations is complicated. For our study, we applied a cut-off of <0.825 µmol RBP/L for children (corresponding to <0.70 µmol retinol/L) [18]. Secondary limitation of RBP is ability to act as a negative acute phase protein; we adjusted for this effect of infection/inflammation by applying a CRP cut-off of >5.0mg /L.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-assay and intra-assay CV of the assay were <10%. Definition of VA status was serum RBP concentration <0.825 µmol/L (biologically equivalent to <0.70 µmol/L retinol) [18].…”
Section: Analysis Of Samples For Retinol Binding Proteinmentioning
confidence: 99%